Immunometabolic Responses after Short and Moderate Rest Intervals to Strength Exercise with and without Similar Total Volume - Agostinete, Ricardo R.; Rossi, Fabrício E.; Magalhaes, Alan José B.; Rocha, Ana Paula R.; Parmezzani, Sérgio S.; Gerosa-Neto, Jose; Cholewa, Jason M.; Lira, Fabio S. (Frontiers in Physiology, 2016)
This study investigated the influence of short and moderate intervals of recovery with and without equated volume during an acute bout exhaustive strength exercise on metabolic, hormonal and inflammatory responses in healthy adults. Eight physically active men (23.5 ±3.1) performed three randomized sequences: Short (70% of 1RM with 30 seconds of rest); Moderate (70% of 1RM with 90 seconds of rest); and Volume-Equated Short (70% of 1 RM with 30 seconds of rest between sets with a repetition volume equal to that performed in Moderate). All sequences of exercises were performed until movement failure in the squat, bench press and T-bar row exercises, respectively. Glucose, lactate, testosterone, IL-6, IL-10, IL-1ra and MCP-1 levels were assessed at rest, immediate post-exercise, and 1 hour post. There was a main effect of time for testosterone (p<0.001). The post hoc indicated differences between post-exercise and rest and post-1 hour and post-exercise (p<0.001). Lactate increased post-exercise when compared to pre and post-1 hour (p<0.001) and maintained higher post-1 hour in relation to rest. IL-6 was greater post-exercise than rest (p= 0.045) and post-1 hour and rest (p= 0.020). IL-10 was greater post-exercise (p= 0.007) and post-1 hour (p=0.002) than rest. IL-1ra increased post-exercise in relation to rest (p=0.003) and MCP-1 was greater post-exercise than rest (p<0.001) and post-1 hour (p=0.043). There were no significant differences between conditions or interaction. Thus, both short and moderate intervals of recovery induced greater metabolic, hormonal and inflammatory responses after acute bout of exhaustive strength exercise in healthy adult.